500 digital illustration hints, tips, and techniques - Herriott, Luke (RotoVision, 2009)
Guides the reader from the basics of digital illustration through to advanced techniques, with sections on the commonly-used software programs, including Photoshop, Painter, Illustrator, Flash, Cinema 4D, and 3D Studio. This comprehensive handbook covers the essential technical considerations of digital illustration.